SCIENTIFIC-PHILOSOPHICAL HERITAGE AND SOCIAL DEVELOPMENT - N. Rakhimbabaeva (European Journal of Humanities and Educational Advancements, 2023)
This article analyzes the contribution of the world-renowned great scientists from our ancient and blessed land to the development of world science and culture with their discoveries and scientific works. Also, attention is paid to the fact that they discovered new directions in science, a new way of thinking, created new doctrines that no one said and could not do before them and that they were scientifically substantiated, as well as their theoretical and practical importance in the social development of Uzbekistan today.